"All of Us Are Unapprehended Felons": Gay Liberation, the Black Panther Party, and Intercommunal Efforts Against Police Brutality in the Bay Area. Issue 3 (12th January 2018) - Leighton, Jared
Abstract: This article shows how the path of the gay liberation movement in the Bay Area was shaped by its relationship to the Black Panther Party (BPP). Previous scholarship has made frequent but brief mention of the connections between the two. However, the Black Panther Party had a greater depth of contact with and longer lasting influence on gay liberation than previously acknowledged, as an examination of movement activism in the Bay Area reveals. Perhaps the central issue of cooperation between gay liberation and the BPP—police brutality—has received little mention. Emerging scholarship is seeking to place LGBT activists in the larger movement against police brutality, and understanding their relationship to the Panthers will be crucial to doing so. While a great range of viewpoints on alliances between the Panthers and gay liberation could be observed in both camps in 1969–1970, many gay activists affirmed a united front even before Newton's statement on gay liberation. Foremost among the reasons for working together was their shared identity as criminalized groups and their shared goal of combating police brutality. Gay liberationists modeled Panther approaches to dealing with police violence, both in armed self-defense and electoral politics, marking a clear break with homophile reformism. In the spring of 1971, both became more moderate and continued along the same path independently, with the issue of police brutality remaining central. This work encourages readers to consider in greater depth the intersection of gay liberation and Black Power, as well as social movements more generally.